Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Simplifying
2x2 + 6x + 4 = 24
Reorder the terms:
4 + 6x + 2x2 = 24
Solving
4 + 6x + 2x2 = 24
Solving for variable 'x'.
Reorder the terms:
4 + -24 + 6x + 2x2 = 24 + -24
Combine like terms: 4 + -24 = -20
-20 + 6x + 2x2 = 24 + -24
Combine like terms: 24 + -24 = 0
-20 + 6x + 2x2 = 0
Factor out the Greatest Common Factor (GCF), '2'.
2(-10 + 3x + x2) = 0
Factor a trinomial.
2((-5 + -1x)(2 + -1x)) = 0
Ignore the factor 2.
Subproblem 1
Set the factor '(-5 + -1x)' equal to zero and attempt to solve:
Simplifying
-5 + -1x = 0
Solving
-5 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '5' to each side of the equation.
-5 + 5 + -1x = 0 + 5
Combine like terms: -5 + 5 = 0
0 + -1x = 0 + 5
-1x = 0 + 5
Combine like terms: 0 + 5 = 5
-1x = 5
Divide each side by '-1'.
x = -5
Simplifying
x = -5
Answer:
Set the factor '(-5 + -1x)' equal to zero and attempt to solve:
-5 + -1x = 0
-5 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
-5 + 5 + -1x = 0 + 5
Combine like terms: -5 + 5 = 0
0 + -1x = 0 + 5
-1x = 0 + 5
Combine like terms: 0 + 5 = 5
-1x = 5
x = -5
Step-by-step explanation:
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.